Development of algorithm for receiving and decoding input signal using MTD decoder for subscriber terminals operating with low-orbit spacecraft - D. P. Sedunov; A. S. Zhunusova (Омский научный вестник)
The relevance of the topic is determined by the need to increase the speed of data transmission in satellite telecommunication systems through the use of noise-proof coding. The speed of data transmission in a radio channel is actually determined by the level of interference present due to the fact that the radio transmission medium is a public environment and other electronic devices operate in it. The purpose of the article is to develop an algorithm for encoding and decoding the input signal using a multithreshold decoder (MTD) of rigid solutions for subscriber terminals operating with low-orbit spacecraft (NCA), and its comparison with a conventional PC decoder «Messi». The comparison allows us to conclude that the application of the developed algorithm is justified in systems where more stringent requirements are imposed on the probability of an error in the communication channel, while the «Messi» decoder is more appropriate to use in the presence of restrictions on computational complexity.